Pelaksanaan Komunikasi Pariwisata Dalam Strategi Pembangunan dan Pengembangan Destinasi Wisata di Kabupaten Samosir (Studi Kasus di Dinas Pariwisata Samosir dan Kelurahan Tuktuk Siadong) - Bantors Sihombing (Akademi Pariwisata Darma Agung, 2018)
The study, entitled implementation of the Communication Strategy In Tourism development and the development of tourist destinations in the County of Samosir (case study in Tourism Samosir Tuk Village and Siadong) intends to unveil on the implementation communication development strategy in tourism development and tourist destinations in the County of Samosir, case studies on Samosir Tourism Office and Neighborhood Tuk Siadong. Research methodology using a qualitative approach. Informant research taken based on purposive sampling, i.e. people who are considered to be competent or meets the criteria of knowing the implementation of tourism communication. From the research found kounikasi tourism is already implemented, but not run effectively. Among other things, government officials apparently do not know Siadong Tuk is a tourist village.